Admission leukocytosis and its implications on intra cerebral haemorrhage - Velayudham, Rajendran; Dasarathan, Ramesh; S., Nirumal Khumar; S., Senthil Kumar (International Journal of Advances in Medicine, 2021)
Background: Intracerebral haemorrhage is one amongst the most common subtype of stroke. It is a catastrophic disease with significant rate of mortality and may lead to severe disabilities. Immediate and effective treatment is a prime requisite of ICH, as rapid mortality occurs within first 24 hours. Definitive diagnosis of ICH is difficult as its symptoms are similar to ischemic stroke. Aim of current investigation was to establish a relationship between intra-cerebral haemorrhage and leukocytosis and to use it as an early tool for detecting haematoma expansion for prognostication and developing newer drugs using a suitable therapeutic target. Methods: Current investigation was an observational study carried out on 100 patients with intra-cerebral haemorrhage. Differential counts were studied with respect to influence of particular subtypes on hematoma expansion. Follow up NCCT was done after 48 hours of the event. Results: Results of present investigation revealed that mean age of the patients was 56 years, 82% were males and all the patients were hypertensive. It was observed that majority of patients with neutrophilic leukocytosis, did not show hematoma expansion and neutrophilic leukocytosis was preferentially present in patients with higher initial bleed volumes. Significant association was observed between monocytosis and haematoma expansion and association between lymphocytosis and volume expansion was observed to be non-significant. Conclusions: Current study findings can aid in early risk stratification and prognostication of ICH patients and can also provide a tool for identification of new therapeutic targets for controlling haematoma expansion.